KEBIJAKAN PENGELOLAAN LIMBAH PLASTIK DI SURABAYA: UPAYA MENGURANGI DAMPAK LINGKUNGAN - Muhayatul, Muhayatul; Frinaldi, Aldri; Rembrandt, Rembrandt; Lanin, Dasman; Umar, Genius (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
This study examines the implementation of plastic bag reduction policies in Surabaya, analyzing their effectiveness and impact on waste management. The research employs a policy implementation approach, utilizing case studies from Surabaya’s traditional markets and official regulations. Data were gathered from journal articles, government regulations, and previous studies related to plastic waste management. The findings indicate that Surabaya has successfully implemented policies such as Perwali No. 16/2022, supported by market-based strategies and public awareness campaigns. The study highlights challenges in enforcement and public compliance while acknowledging the city’s achievements, such as winning the Adipura Kencana award. The results suggest that strengthening policy enforcement and community participation is essential for sustaining long-term environmental benefits.